Correlation between Chest X-ray and Non Severe Pneumonia as per WHO Guidelines - Mishra, Rakesh; Parihar, Harlal; Kumar Dubey, Arvind; Abdul Khader, Kurnal (International Journal of Medical Research and Review, 2014)
Introduction: Pnemonia or lower respiratory tract infections are considering most common entity responsible for under five morbidity & mortality. WHO guidelines for ARI control programme is universally accepted by most of countries. It has reduced mortality by proper treatment and referral. Although tachypnia is consider single criteria for diagnosis. Many of these children have viral pneumonia or normal x-ray. Although oral antibiotics are prescribed to them but it is actually not needed. Methods: All the patients came to paediatric department from January 2013 to July 2014 & diagnosed as pneumonia as per WHO protocol were included in study. It was a prospective, double blind, randomized controlled study of radiological data of all the patients who were diagnosed as pneumonia as per WHO protocol. All the x- rays were read by two experts. Results: Of 219 radiographs examined 23 have evidences of pneumonia. 183 patients have normal x-ray. Conclusion: Radiology is consider most accurate method for diagnosis of pneumonia. As per WHO protocol these children receive unnecessary antibiotics although many of these children have viral pneumonia. There is need of some cheaper, easily available & more accurate methods to identify etiological organism for pneumonia.